Preparation of superhydrophobic sponge and its application in oil-water separation and treatment of polymer-containing wastewater - Fang, Liuya; Xu, Hui; Fan, Zhihai; Duan, Xiaopeng; Wang, Qing; Bai, Xiaoliang; Peng, Jiao; Jin, Shiwei (Frontiers in Bioengineering and Biotechnology, 2023)
At present, the application prospect of superhydrophobic materials in oil-water separation, an-tibacterial and other aspects have attracted more and more attention. However, preparing a simple and low-cost superhydrophobic material remains a challenge. Using acetone as solvent, candle soot, silver/silica nanoparticles and polydimethylsiloxane were uniformly mixed to form a mixed solution, and the superhydrophobic sponge was successfully prepared by spraying method. The results show that the superhydrophobic sponge has high water contact Angle (162°) and excellent oil-water separation efficiency, which can realize effective treatment of polymerized wastewater. In addition, the superhydrophobic sponge showed better antibacterial properties on the surface of Escherichia coli and Staphylococcus aureus. In this work, a simple way to prepare superhydro-phobic oil-water separation material is proposed. The preparation process is green, the material is easy to obtain, and it is expected to be widely used in practical production.